Некоторые прикладные модели прочностной надежности при внезапных отказах - Гринченко, А. С. (НТУ "ХПИ", 2003)
The mode of a schematization are real casual process loading is offered which thus will be transformed to a discrete sequence statistically of independent overloads. The definition of probability durability is considered at a multiplis operation of overloads. Some analytical models convenient at execution of practical accounts of elements machines and constructions on durability reliability are obtained
Keywords: модели деградационных отказов; модели внезапных отказов; распределение Вейбулла; перегрузка